The Affordability of School Textbooks in Kenya: Consumer Experiences in the Transformation to a Liberalising Economy (Nordic Journal of African Studies, 2004)
The growth of educational publishing in Kenya depends heavily on the disposable income of its customers. This article looks at the incomes of both actual and potential customers and how they prioritise their spending. The findings are based on research carried out in Kenya by the author. In selecting the areas to conduct the research, socio-economic factors, geographical conditions and level of development were considered. It was found that most textbook purchasers think that textbooks are very expensive in comparison with their own incomes. This has therefore led them to prioritise basic essential needs before thinking of purchasing textbooks.